Joint contribution and consumption through online crowdfunding campaigns - Fan-Chuan Tseng (Cogent Business & Management, 2020)
With the emergence of online social networks and entrepreneur projects, crowdfunding is gaining popularity to raise money for a new project. In the online crowdfunding platform, the members (including project initiators and supports) share ideas to solve a problem and create favourable exchange conditions for the individuals' as well as social benefits. In this study, an extended expectancy confirmation model is proposed and validated to explore the influence of supports' individual traits, consumer values as well as their evaluation of the crowdfunding projects. Through the online questionnaire survey and quantitative analysis, the results show significant antecedents of supports' confirmation and identify the influence of consumption value on satisfaction and future intention of online crowdfunding. This study suggests that the success of online crowdfunding campaign is not just derived from individuals' prosocial orientation. Instead, consumers' trait and cognition should be addressed so as to increase the benefits of collective action.
Keywords: 650; online crowdfunding; expectancy confirmation theory; consumer innovativeness; consumer identification; consumption value